Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/int.22790
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive complex network topology with fitness distance correlation framework for particle swarm optimization

Abstract: The particle swarm optimization algorithm is an effective tool to solve various optimization problems due to the small number of parameters and the simple learning strategy. However, the updated strategy from the basic PSO mainly aims to learn the global optimal particles, and it often leads to premature convergence with poor solution accuracy. An adaptive complex network topology with a fitness distance correlation for the particle swarm optimization algorithm is proposed (CNAPSO). Using the CNAPSO algorithm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In MPSO/D, 13 the author proposed a MOPSO based on the target space decomposition, which decomposes the target space into several subregions on the basis of a set of uniformly distributed directional vectors. In CNAPSO, Li et al 32 proposed an adaptive complex network topology algorithm with fitness distance correlation. Using the CNAPSO algorithm, it is concluded that different network topologies have different degrees of discreteness in the search process of PSO.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In MPSO/D, 13 the author proposed a MOPSO based on the target space decomposition, which decomposes the target space into several subregions on the basis of a set of uniformly distributed directional vectors. In CNAPSO, Li et al 32 proposed an adaptive complex network topology algorithm with fitness distance correlation. Using the CNAPSO algorithm, it is concluded that different network topologies have different degrees of discreteness in the search process of PSO.…”
Section: Research Backgroundmentioning
confidence: 99%
“…A complex network can be defined as a network with some or all properties of self-organization, self-similarity, attractiveness, small world, and scale-free, and all complex networks can be abstracted into the topology of nodes and edges [1][2] . Watts and Strogatz [3] in 1998 proposed a WS small-world network with a large cohesion coefficient and a small average path length, which makes the formed network more and more close to the real world.…”
Section: Introductionmentioning
confidence: 99%
“…The robots are programmed to act while perceived values are lower or higher than a particular value. The programmers start their idea by drawing a fl ow chart and then design appropriate algorithms to reduce the complexity and iteration of their program [1][2][3][4]. Logic circuits, electronic components and programming are the essential parts of a robot.…”
Section: Introductionmentioning
confidence: 99%